Immunomodulatory Effects of Chitotriosidase Enzyme - Elmonem, Mohamed A. (Enzyme Res, 2016)
Chitotriosidase enzyme (EC: 3.2.1.14) is the major active chitinase in the human body. It is produced mainly by activated macrophages, in which its expression is regulated by multiple intrinsic and extrinsic signals. Chitotriosidase was confirmed as essential element in the innate immunity against chitin containing organisms such as fungi and protozoa; however, its immunomodulatory effects extend far beyond innate immunity. In the current review, we will try to explore the expanding spectrum of immunological roles played by chitotriosidase enzyme in human health and disease and will discuss its up-to-date clinical value.